Adoption and implementation of produce prescription programs for under-resourced populations: clinic staff perspectives - Folta, Sara C.; Li, Zhongyu; Cash, Sean B.; Hager, Kurt; Zhang, Fang Fang (Frontiers in Nutrition, 2023)
Background. Produce prescription programs represent a promising intervention strategy in the healthcare setting to address disparities in diet quality and diet-related chronic disease. The objective of this study was to understand adoption and implementation factors related to these programs that are common across contexts and those that are context-specific. Methods. In this qualitative case comparison study, we conducted qualitative interviews with eight clinic staff from five primary care “safety net” clinics, identified by a partnering non-profit organization that operated the programs, in April-July 2021. Results. Across clinics, the ability to provide a tangible benefit to patients was a key factor in adoption. Flexibility in integrating into clinic workflows was a facilitator of implementation. Fit with usual operations varied across clinics. Common challenges were the need for changes to the workflow and extra staff time. Clinic staff were skeptical about the sustainability of both the benefits to patients and the ability to continue the program at their clinics. Discussion. This study adds to a growing body of knowledge on the adoption and implementation of produce prescription programs. Future research will further this understanding, providing the evidence necessary to guide adopting clinics and to make informed policy decisions to best promote the growth and financial sustainability of these programs.